FACTORS ASSOCIATED WITH THE REMINERALIZATION EFFECTIVENESS OF CASEIN PHOSPHOPEPTIDE-AMORPHOUS CALCIUM PHOSPHATE ON MOLAR-INCISOR HYPOMINERALIZATION AFFECTED TEETH: A SYSTEMATIC REVIEW (Vietnam Journal of Community Medicine, 2026)
Objectives: This systematic review aimed to synthesize and analyse factors affecting the remineralizing effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) on molar-incisor hypomineralization (MIH) affected teeth.Methods: The study followed the PRISMA guidelines and had the PICO criteria. A comprehensive search was conducted across four databases: PubMed, Google Scholar, Cochrane, and Embase and complemented by manual search.Results: A total of 18 articles were selected, including 10 randomized controlled trial, 6 in vitro studies, and 2 non-randomized clinical trials. Among the in vitro studies, 3/6 studies indicated that CPP-ACP and CPP-ACFP had superior remineralization efficacy on white lesions compared to yellow lesions during short-term follow-up. 2/6 studies showed that CPP-ACFP resulted in greater remineralization of yellow lesions over long-term follow-up. 1 study highlighted that CPP-ACFP achieved faster remineralization than CPP-ACP on yellow lesions during the initial phase. Additionally, 3 studies found that the inclusion of fluoride in CPP-ACP did not result in a significant difference in remineralization efficacy during long-term follow-up.Conclusion: CPP-ACFP is more effective at remineralizing white spot lesions than yellow lesions in the early stages. While fluoride accelerates the initial rate of remineralization, no significant difference in long-term efficacy is observed.